Keep an Ear Out for Francisella tularensis: Otomastoiditis Cases after Canyoneering - Guerpillon, Brice; Boibieux, Andre; Guenne, Clemence; Ploton, Christine; Ferry, Tristan; Maurin, Max; Forestier, Emmanuel; Dauwalder, Olivier; Manipoud, Patrick; Ltaïef-Boudrigua, Aicha; Gürkov, Robert; Vandenesch, Francois; et al. (Frontiers in Medicine, 2016)
We report here three unusual cases of otomastoiditis due to Francisella tularensis, complicated by cervical abscesses and persistent hearing loss, plus facial paralysis for one patient. Intriguingly, the three patients had practiced canyoneering independently in the same French river, between 2009 and 2014, several days before clinical symptoms onset. The results point out that fresh water exposure may be a potential contamination route for tularaemia. Besides, due to the frequent complications and sequelae, we believe that Francisella tularensis should be considered as a possible aetiology in case of otitis media, failure of the conventional antibiotic treatment and suspicious exposure of the bacteria.